Permeability of dental gloves after exposure to certain dental materials - Chua, Angela Grace SM
Infection control and universal precaution are an integral part in any treatment procedure in the dental profession. To ensure safety of both patient and dentist, integrity of the barrier for protection must not be compromised. The aim of the study is to determine through spectrophotometric analysis, which type of glove, latex or vinyl, show increased permeability after 15-minute exposure to petroleum jelly and sodium hypochlorite. An erythrosine dye permeability test on 48 randomly selected gloves (24 for each type) was done to check for the degree of permeability after exposure. Baseline test was done to check for presence of leaks or perforations. Each glove type was exposed to the dental material for 15 minutes and washings were read every 30, 60, 90, 120-minute time intervals. The results were compared with the unexposed gloves group. Statistical analysis was done based on a 0.05 level of significance. The concentrations after 30, 60, 90 and 120 minute intervals showed an increasing trend in permeability for both glove types after exposure to both dental materials although this difference is also not statistically significant. The difference between the mean percent absorption of both types of gloves was not significant, neither is the difference as to which dental material caused greater permeability on both glove types. There was, however, a statistically significant increase in permeability for both glove types after exposure to the two dental materials compared to both types of unexposed glove samples.